Air‐sea CO2 fluxes above the stratified oxygen minimum zone in the coastal region off Mexico. Issue 5 (14th May 2014) - Franco, Ana C.; Hernández‐Ayón, J. Martín; Beier, Emilio; Garçon, Veronique; Maske, Helmut; Paulmier, Aurelien; Färber‐Lorda, Jaime; Castro, Rubén; Sosa‐Ávalos, Ramón
Abstract Oxygen minimum zones (OMZs) are important sources of CO2 to the atmosphere when physical forces bring subsurface water with high dissolved inorganic carbon (DIC) to the surface. This study examines, for the first time, the influence of the OMZ of the coastal North Eastern Tropical Pacific off Mexico on surface CO2 fluxes. We use variations in the oxycline depth and subsurface water masses to discern physical oceanographic influences. During two cruises, in November 2009 and August 2010, DIC and total alkalinity (TA) measurements were used to estimate pCO2 and air‐sea CO2 fluxes. At the OMZ layer, Subtropical Subsurface Water (StSsW) was found to have high pCO2 values (1290 ± 70 μatm). Due to strong vertical stratification, however, the relationship between ΔpCO2 at the air‐sea interface and the oxycline/StSsW upper limit depth was weak. During November, the region was a weak source of CO2 to the atmosphere (up to 2.5 mmol C m−2 d−1), while during August a range of values were observed between −4.4 and 3.3 mmol C m−2 d−1). Strong stratification (>1200 J m−3) prevented subsurface mixing of water from the OMZ to the upper layer; particularly in November 2009 which was during an El Niño event. Results suggest that advection of surface water masses, reinforced by strong vertical stratification, controlled surface pCO2, and air‐sea CO2 fluxes.